With multiple years of on-station and on-farm testing, WRI, Faisalabad, and AZRI, Bhakhar, BARI, Chakwal have recently released five varieties, namely,: Subhani 2021, MH-2021, and Dilkash-2021, Bhakkar-20 and MA-2020, respectively. - CGIAR Research Program on Wheat (2020)
Seed multiplication of these varieties have been implemented aggressively to access new seeds to small farmers